Private regulation and the internal market : sports, legal services, and standard setting in EU economic law - Mataija, Mislav (Oxford : Oxford University Press, 2016)
How does EU internal market law, in particular the rules on free movement and competition, apply to private regulation? Through a close analysis of three case studies (sports, the legal profession, and standard-setting) this book studies how internal market law is used as a control mechanism over private regulators.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 25, 2016).
Keywords: Trade regulation -- European Union countries; Civil rights -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law